Modeling the effects of physical activity and lifestyle on academic achievement: The mediating roles of physical fitness and self-confidence - Saraswara, Bella Shasi; Maksum, Ali; Priambodo, Anung; Turi, Moh; Iskandar, Risfan (Edelweiss Applied Science and Technology, 2025)
This study developed and tested a theoretical model to explain the complex relationships between physical activity, lifestyle, fitness, self-confidence, and academic success. Employing a cross-sectional methodology, data were collected from 260 tenth-grade public high school students in Surabaya, Indonesia, selected through cluster random sampling. The measures included the International Physical Activity Questionnaire (IPAQ) for physical activity, the Healthy People Lifestyle Profile II (HPLP II) for lifestyle assessment, the Lauster scale for self-confidence evaluation, the beep test and bioelectrical impedance analysis for physical fitness assessment, and report card grades for academic performance. Data analysis was conducted using structural equation modeling. The principal findings reveal that physical exercise significantly impacted students’ physical fitness, with intensity being a key factor. Additionally, lifestyle played an essential role, particularly in stress management and health accountability. Physical fitness was found to strongly influence self-confidence, which in turn had a substantial direct impact on academic performance. Importantly, physical fitness was shown to affect academic performance indirectly through the mediation of self-confidence, especially in physical education and science subjects. The formulated theoretical model demonstrated a significant alignment with the empirical data. These observations highlight the importance of educational strategies that integrate both physical and psychosocial aspects to effectively enhance academic performance and promote well-rounded, self-assured student identities.